Validity and reliability of a 10 Hz GPS for assessing variable and mean running speed - Bataller-Cervero, A. V.; Gutierrez, H.; DeRenteria, J.; Piedrafita, E.; Marcén, N.; Valero-Campo, C.; Lapuente, M.; Berzosa, C. (Journal of Human Kinetics, 2019)
Our purpose was to assess the 10 Hz Viper GPS devices` validity and reliability (STATSport) in both instantaneous and mean speed measuring in accelerations and decelerations in straight-line running conditions. Eight amateur team sport players participated in the study, performing firstly 21 x 40 m sprints at submaximal incremental speed, and secondly 21 x 40 m sprints, with the first stage consisting of submaximal incremental speed, and the second stage of subsequent submaximal decreasing speed. Criteria systems used to evaluate the GPS validity were a radar gun for instantaneous speed, and timing-gates for mean speed. Reliability was measured with two GPS devices carried by the same athlete, running 10 x (20 m + 20 m) sprints with a 180º change of direction and a 10 s inter-set rest interval. Results showed an agreement between GPS devices and the criteria systems measuring instantaneous speed (r = 0.98; standardized mean bias (SMB) = -0.07; standard typical error (STE) = 0.22) and mean speed (r = 0.99; SMB = 0.38; STE = 0.17). The reliability study presented a nearly perfect correlation between devices, a trivial SMB and a small STE (r = 0.97; SMB = 0.04; STE = 0.23). 10 Hz GPS devices are an adequate solution to monitor straight-line running speed in acceleration and deceleration conditions, but we would like to draw attention to the small errors and bias detected, such as the speed overestimation compared with timing gates.